Novel human ABCC9/SUR2 brain‐expressed transcripts and an eQTL relevant to hippocampal sclerosis of aging. (15th July 2015) - Nelson, Peter T.; Wang, Wang‐Xia; Wilfred, Bernard R.; Wei, Angela; Dimayuga, James; Huang, Qingwei; Ighodaro, Eseosa; Artiushin, Sergey; Fardo, David W.
Abstract: ABCC9 genetic polymorphisms are associated with increased risk for various human diseases including hippocampal sclerosis of aging. The main goals of this study were 1 > to detect the ABCC9 variants and define the specific 3′ untranslated region (3′UTR) for each variant in human brain, and 2 > to determine whether a polymorphism (rs704180) associated with risk for hippocampal sclerosis of aging pathology is also associated with variation in ABCC9 transcript expression and/or splicing. Rapid amplification of ABCC9 cDNA ends (3′RACE) provided evidence of novel 3′ UTR portions of ABCC9 in human brain. In silico and experimental studies were performed focusing on the single nucleotide polymorphism, rs704180. Analyses from multiple databases, focusing on rs704180 only, indicated that this risk allele is a local expression quantitative trait locus (eQTL). Analyses of RNA from human brains showed increased ABCC9 transcript levels in individuals with the risk genotype, corresponding with enrichment for a shorter 3′ UTR which may be more stable than variants with the longer 3′ UTR. MicroRNA transfection experiments yielded results compatible with the hypothesis that miR‐30c causes down‐regulation of SUR2 transcripts with the longer 3′ UTR. Thus we report evidence of complex ABCC9 genetic regulation in brain, which may be of direct relevance to human disease. ABCC9 gene variants are associated with increased risk for hippocampal sclerosis of aging (HS‐Aging – a prevalent brain disease with symptoms that mimic Alzheimer's disease). We describe novel ABCC9 variants in human brain, corresponding to altered 3'UTR length, which could lead to targeting by miR‐30c. We also determined that the HS‐Aging risk mutation is associated with variation in ABCC9 transcript expression. Abstract : ABCC9 gene variants are associated with increased risk for hippocampal sclerosis of aging (HS‐Aging – a prevalent brain disease with symptoms that mimic Alzheimer's disease). We describe novel ABCC9 variants in human brain, corresponding to altered 3'UTR length, which could lead to targeting by miR‐30c. We also determined that the HS‐Aging risk mutation is associated with variation in ABCC9 transcript expression.